Validazione e standardizzazione del questionario «Quin - Quando insegno» - Pietro Lucisano; Emanuela Botta (LED Edizioni Universitarie, 2023)
Validation And Standardization Of The Questionnaire «Quin - When I Teach» The professionalism of a teacher is the topic of a wide-ranging debate aimed at overcoming crises of confidence in this category and reaffirming the teacher as a valuable source for students' growth and cognitive and socio-emotional development. This questionnaire shows the validation and standardization process of a self-perception instrument aimed at teachers and designed to explore some of the main dimensions of teaching that, overcoming the limitations found in the literature, highlights the need to encourage teachers to reflect on themselves in their work. The tool can be used both by individual teachers and by schools as support in their self-evaluation processes. The information that emerges can be shared within the educating community to orient work and teaching practices in a specific school context. In perspective, the tool will be used in combination with others, intended for teachers and students, and accessible via a dedicated digital platform. The system as a whole will allow us to detect experiences, needs and requirements aimed to focus on the good practices implemented and to design targeted improvement actions.